Paradigm shift in surgery for benign parotid tumors: 19 years of experience with almost 3000 cases - Bär, Bianca; Mantsopoulos, Konstantinos; Iro, Heinrich (Laryngoscope, 2019)
Objectives: The aim of this study was to explore the changes in philosophy in the surgical therapy of benign parotid tumors over a period of 19 years. Methods: The records of all patients treated for benign parotid tumors between 2000 and 2018 were evaluated. Data were analyzed with respect to the number of procedures carried out per year of the study according to each of the different surgical modalities and the incidence of postoperative complications. Statistical analysis was performed using the x2 test. A P value of <.05 was considered statistically significant. Results: A total of 2988 patients were included in this study. Our analysis showed that the increasing performance of extracapsular dissection was associated with a progressive reduction in the incidence of temporary facial nerve palsy and Frey's syndrome, while the rate of permanent facial nerve palsy remained consistently low. Conclusion: One of the most controversial issues in head and neck surgery is which therapeutic approach is best in patients with benign parotid tumors. Our analysis demonstrated that a change of strategy towards reducing invasiveness was possible, with exceptional functional results. Avoidance of facial nerve dissection is feasible in more than two-thirds of cases with benign tumors. Level of Evidence: 4b. Laryngoscope, 2019.
CRIS-Team Scopus Importer:2019-12-17
Keywords: complete parotidectomy; Extracapsular dissection; facial nerve; Frey's syndrome; superficial parotidectomy